Analysis of Children's Character Education and Anti-Violence Policies in Indonesia - Muhammad Al Mighwar; Syifa Rahmawati (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2023)
Acts of violence are basically behavior that will harm other people, such as discrimination, exploitation, both economic and sexual, neglect, cruelty, abuse, injustice and other wrongful treatment. Policy in education in Indonesia is based on the rules that apply and are able to be obeyed by each individual, so early level violence will be easily realized in stages depending on parenting patterns in the family environment and also in the school environment. With the most important effort, namely getting used to being honest with your child, your child's future will be able to go according to what is expected. With an attitude of honesty, it is not impossible for students to become stronger, there will be no deep lies to create trouble in every future behavior. Associating with honesty and direction in every environment motivates and inspires children to grow well.